2021
DOI: 10.1177/1055665621996115
|View full text |Cite
|
Sign up to set email alerts
|

Response to Pulp Vitality Tests in Teeth Submitted to Orthodontic Movement, Adjacent to the Cleft Area

Abstract: Objective: To evaluate the pulp vitality in teeth adjacent to the cleft area submitted to orthodontic movement into the alveolar graft area in individuals with complete unilateral cleft lip and palate (CUCLP). Design: Cold sensitivity, vertical, and horizontal percussion tests were conducted on the teeth adjacent to the cleft and the contralateral teeth. Setting: Endodontics Sector in the Hospital for Rehabilitation of Craniofacial Anomalies, University of São Paulo (HRAC/USP). Patients: One hundred patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Though very few studies suggested that heavy forces can lead to loss of tooth vitality but there are not enough evidences to support this fact 11 . Most of the other studies have shown that there might be changes in pulpal blood flow, hyperemia or oxygen saturation but no long term effect on pulp vitality 9,[12][13][14] The study has shown that even with heavy intrusive force there is no change in vitality of dental pulp in normal teeth but teeth having history of previous trauma are more susceptible to pulpal necrosis 15 . Traumatized incisors, especially maxillary lateral incisors have high chance of pulpal necrosis during orthodontic intrusion than normal teeth 15 .…”
Section: Effect Of Orthodontic Force On Pulpmentioning
confidence: 99%
“…Though very few studies suggested that heavy forces can lead to loss of tooth vitality but there are not enough evidences to support this fact 11 . Most of the other studies have shown that there might be changes in pulpal blood flow, hyperemia or oxygen saturation but no long term effect on pulp vitality 9,[12][13][14] The study has shown that even with heavy intrusive force there is no change in vitality of dental pulp in normal teeth but teeth having history of previous trauma are more susceptible to pulpal necrosis 15 . Traumatized incisors, especially maxillary lateral incisors have high chance of pulpal necrosis during orthodontic intrusion than normal teeth 15 .…”
Section: Effect Of Orthodontic Force On Pulpmentioning
confidence: 99%
“…Depending on the extent, the bone defect can be seen as a radiolucent area surrounding the periapical portion of teeth adjacent to the cleft. This evidences the importance of performing adequate anamnesis, physical and complementary exams for an accurate diagnosis 2,3 .…”
Section: Introductionmentioning
confidence: 95%